The Influence Of Transformational Leadership On Employee Performance With Organizational Commitment As An Intervening Variable (A Case Study at PT. XYZ) - Firdaus, Shafira Maharani; Prahiawan, Wawan; Lutfi, Lutfi (Advances In Social Humanities Research, 2025)
This study aims to analyze the influence of transformational leadership on employee performance with organizational commitment as an intervening variable. This study was conducted on PT XYZ employees who work in a shift system, with a sample of 136 respondents. The research approach used is quantitative with survey methods and causality analysis. The data analysis technique was carried out using variant-based Structural Equation Modeling (SEM) with the help of SmartPLS software version 4.1.1.2. The results of the study show that transformational leadership has a positive and significant effect on employee performance, which means that transformational leaders are able to increase work effectiveness and productivity. In addition, transformational leadership also has a positive and significant effect on organizational commitment, which reflects that leaders who provide motivation and inspiration are able to increase employee attachment to the company. Furthermore, organizational commitment has a positive and significant effect on employee performance, which indicates that employee loyalty and belonging drive improved work performance. These findings confirm that the influence of leadership on performance does not only occur directly, but also indirectly through increased organizational commitment. Therefore, companies need to strengthen the role of transformational leadership as a strategy to build commitment and drive optimal employee performance